Effects of Some Heavy Metals (Cd, Cu, Pb, and Zn) Concentration on Qualitative Traits of Dill (Anethum graveolens L.) and Basil (Ocimum basilicum L.) - Amir RAHİMİ; Gülen ÖZYAZICI; Fatemeh AHMADİ (ISPEC Journal of Agricultural Sciences, 2020)
Soil pollution is a global concern from past to recent. Toxic and high resistance nature of chemical pollutants, such as heavy metals show their important as environmental risk and a serious problem for human health, because they can introduce to the food chain from contaminated environments. Experiments were conducted to evaluate the effect of Cd, Cu, Pb, and Zn on qualitative parameters of dill (Anethum graveolens L.), and basil (Ocimum basilicum L.) grown in polluted soil environment. Heavy metals concentration, total phenol and flavonoid, essential oil percentage, DPPH radical scavenging activity, super and nitric oxide radical scavenging activity in leave and stem parts of the plants were analysed in this study according to standard methods. According to results, Cu was the dominant heavy metal in leave and stem of both studied plants, followed by Pb, Zn, and Cd. The concentration of various heavy metals in dill was more than two times higher than basil. Total phenol and flavonoids showed significant differences in leave and stem in both plants. DPPH, super oxide and nitric oxide radical scavenging activity showed significant higher values in leave than stem in both plants.